Quality changes of acerola fruit harvested at different maturity stages and exposed to external ethylene - Silva Ribeiro, Bruna; Rodrigues Ferreira, Maria Aparecida; Dias Nascimento, Pedro Henrique; Moura, Nadiane Raquel; Souza Silva, Danielly; Tonetto de Freitas, Sérgio (Revista Ceres, 2023)
Although acerola (Malpighia emarginata D.C.) has been suggested to be a climacteric fruit, little is known about its sensitivity to exogenous ethylene. The objective of the study was to evaluate the quality changes of acerola fruit at two harvest maturity stages in response to external ethylene application. ‘Flor Branca’ and ‘Junko’ acerolas were harvested at the maturity stages 1 (green fruit with density>1 g cm-3) and 2 (green fruit with density <1 g cm-3) and were treated with 0 or 1,000 μL L-1 of ethylene for 24 hours at 12 oC.The fruit were stored at 12oC with relative humidity of 90-95% for 14 days. Both cultivars harvested at the maturity stage 2 showed skin color change from green to red during storage, which was not observed in fruit harvested at the maturity stage 1. External ethylene had no effect on ‘Flor Branca’ and ‘Junko’ acerolas respiration rate, flesh firmness, skin color, weight loss, soluble solids (SS), titratable acidity (AT), SS/AT ratio, and ascorbic acid contents. The classification of green acerolas by density was an effective approach to determine fruit harvest maturity for fresh consumption.